PENGGUNAAN MEDIA POP-UP BOOK DALAM PEMBELAJARAN TEMATIK-INTEGRATIF (TEMA MITIGASI BENCANA) - Andriani, Rori Maulia; Putra, Muhammad Jaya Adi; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the process of developing and using pop-up book media in learning about disaster mitigation themes at SDN 008 Tambang District, Kampar Regency. This research was conducted at SDN 008 Tambang District, Kampar Regency in October - November 2019. This type of research is development research, adapting the ADDIE development model which consists of five stages which include analysis, design, development. , implementation (implementation) and evaluation (evaluation). Two trials were carried out namely individual trials and limited trials to then be further implemented with improvements to the broad implementation test. Based on the results of the study it can be concluded that the pop-up book media on the theme of disaster mitigation as a whole reaches a percentage of 70.72% with a fairly good category and the pop-up book media is more suitable to be used madniri or small groups.Key Words: Learning Media, Pop-up Book, Disaster Mitigation